(untitled) (Agricultural Engineering, 2016)
The aim of the study was to determine the effect of manure cooling by the use of the heat recovery system on odour emission from a deep litter piggery. Annual comparative research was carried out in a twin-room deep litter piggery located in Wielkopolska Voivodeship. The recovered heat was transferred to central heating and domestic hot water systems of a residential building. The study showed that the average odour emission rate from the room, where heat was recovered (0.192±0.083 ouE·s−1·kg m.c.−1) was lower than in the room without heat recovering (0.273±0.138 ouE·s−1·kg m.c.−1) (p<0.05). The difference was 27%. It was also found that there was statistically significant strong correlation (r=0.86) between the amount of the recovered heat and the percentage odour emission reduction (p<0.05). This relationship was described by the logarithmic regression line y=12.5ln(x)-21.5 (r2=0.74)